Portofolio saham teknologi “ekonomi baru” berbasis distribusi probabilitas - Ellen Pinkan Rolos; Seren Onibala (Yayasan Widyantara Nawasena Raharja, 2023)
Global issues are a challenge, especially for stocks in the technology sector. Tech stocks, especially on the “new economy” trading boards, are stocks that investors tend to be interested in because they are on par with the main trading boards. This study aims to examine the probability of return and risk-return tradeoff from BELI, BUKA, and GOTO in order to determine optimal returns with measured risk. This study finds that GOTO has the highest Sharpe Ratio. The result indicates that GOTO has a better risk-return tradeoff compared to other firms. In addition, the results of the probability distribution analysis show that GOTO tends to have a small chance of obtaining a low rate of return compared to other firms.